Surprising Institutions - Carl Hampus Lyttkens (Lund University, School of Economics and Management, Department of Economics, 2012)
This paper introduces the notion of surprising institutions. Because we often carry incorrect beliefs about the world surrounding us and we are therefore often mistaken about the nature of the institutional structure facing us. The story told in this paper shows that an institution may come as a surprise, even though its origins lies some 500 years back, and that the information we receive as feedback on our actions does not necessarily improve our understanding of the institutional structure. It turns out that it is possible for an "ordinary citizen" to win a case against a multinational corporation, and against a government agency with more than 350 years on its neck (what a surprise!) but it also transpires that even if you win, you lose (not quite a surprise).
Keywords: H11; K11; 330; institutions; beliefs; surprise; feedback; property rights